Estimulación Temprana y Desarrollo del Lenguaje en Niños de Nivel Inicial de la Escuela de Educación General Básica “Teniente Hugo Ortiz” periodo 2023-2024 - Chalan Abrigo, Gilda Patricia (2024)
This curricular integration paper entitled: Early stimulation and language development in children at the beginners’ level from the Educación General Básica “Teniente Hugo Ortiz” School for the period 2023-2024, aims to analyse the influence of early stimulation on the prevention of linguistic problems in children at the beginners’ level. It is a qualitative, descriptive, non-experimental and cross-sectional study. In order to reach the objectives, we applied two instruments, an interview addressed to the teacher, and an observation sheet which allowed the collection of trustworthy and necessary information, thus evidencing the following information: there is indeed an early stimulation influence, which aids the language problems prevention in the children growing process. Besides, there are some favourable factors that stimulate language development such as: multisensory activities, games, exercises, new vocabulary implementation, pictograms, songs, rhymes drilling and reading of stories; however, some main problems were also identified: overprotection, the family environment, lack of stimulation, lack of new vocabulary, all of which interfere with good language development in children at the beginners’ level. Also through observation technique, it was possible to evidence that the teacher uses early stimulation strategies, since children are exposed to games, story projection, pictogram reading, rhymes, songs, story reading, among others; therefore, there is no absence of early stimulation for language development in children at the beginners’ level, which allows us to conclude that; early stimulation has a positive influence on the prevention of language problems in children at the beginners’ level from the Educación General Básica “Teniente Hugo Ortiz” School. Key words: Language, Stimulation, Techniques, Development, Benefits.